Reconstructing Child Custody Law in Indonesian Religious Courts: Integrating Islamic Law, Child Rights, and Substantive Justice - Lina Nur Anisa (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
This study aims to propose a comprehensive model for reconstructing child-custody law in Indonesia’s religious courts by integrating Islamic family law, children’s rights, and substantive justice. Utilising a hermeneutic and descriptive-analytical approach to library research, the study analyses legal texts, court decisions, and relevant literature. The results reveal significant gaps between legal norms and actual judicial practices, particularly regarding the prioritisation of gender biases and legal formalities over child welfare. The study identifies that child custody decisions often overlook universal child protection principles and fail to consider substantive justice. The proposed model advocates for legal reforms, including enhancing judicial capacity, integrating psychological assessments, and promoting restorative justice in dispute resolution. This research contributes to family law reform by providing a comprehensive framework that centres child welfare in custody decisions, aiming for a more responsive and just legal system. Furthermore, it offers both conceptual and practical guidance to improve child protection in Indonesia’s family courts, address contemporary societal needs, and advance an inclusive, child-centred family law that balances progressive values with cultural sensitivity. The findings emphasise the importance of cross-sector collaboration in implementing these reforms, urging policymakers, judges, and child protection agencies to work together for the betterment of child welfare in legal proceedings.